2019
DOI: 10.1007/s00216-019-02217-y
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale metal–organic frameworks as key players in the context of drug delivery: evolution toward theranostic platforms

Abstract: Introduction3 Key features of MOFs for drug delivery 6 Types of MOF-based drug delivery systems 8 Non-controllable MOF-based DDS 9 Single stimulus-responsive MOF-based DDS 11 Multiple stimuli-responsive MOF-based DDS 18Multifunctional MOF-based theranostic platforms 20 Challenges and perspectives 25Conclusions 27References 28

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 155 publications
(193 reference statements)
0
36
0
Order By: Relevance
“…In current research, MOF materials are mainly used in energy-storage, gas adsorption and separation, catalysis, sensing, magnetism, and fluorescence applications. Carrillo-Carrión [ 19 ] reported that MOFs have emerged as one of the most fascinating libraries of porous materials with a large potential in very diverse application areas. Huang et al [ 20 ] synthesized bimetallic Ce–Ni MOFs (Ce–Ni-MOFs) via hydrothermal reactions using 1,3,5-benzenetricarboxylic acid as a ligand.…”
Section: Introductionmentioning
confidence: 99%
“…In current research, MOF materials are mainly used in energy-storage, gas adsorption and separation, catalysis, sensing, magnetism, and fluorescence applications. Carrillo-Carrión [ 19 ] reported that MOFs have emerged as one of the most fascinating libraries of porous materials with a large potential in very diverse application areas. Huang et al [ 20 ] synthesized bimetallic Ce–Ni MOFs (Ce–Ni-MOFs) via hydrothermal reactions using 1,3,5-benzenetricarboxylic acid as a ligand.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 , 5 , 6 The ability to control particle size, 7 , 8 , 9 surface chemistry, 10 and internal porosity 11 , 12 has led to increasingly complex MOF-based materials. These have been designed to target specific cells 13 and organelles, 14 transport large specialized cargo such as oligonucleotides and proteins, 15 , 16 , 17 , 18 , 19 release these in response to specific stimuli, 20 , 21 and combine drug delivery with other techniques such as imaging 22 , 23 , 24 , 25 , 26 or photodynamic therapy. 27 , 28 Despite this diversification of material, the process of postsynthetic drug loading itself is often undercharacterized; cargo is often simply assumed to penetrate the porosity of the MOF despite potential competition from loading solvents.…”
Section: Introductionmentioning
confidence: 99%
“…171,[178][179][180][181] In the particular case of PDT, the main advantages of MOFs can be summarized as follows: 180,181 (i) their exceptional structural and compositional tunability allows the incorporation of a myriad of PSs with a high PS loading capacity thanks to their remarkable high surface area; (ii) their structural regularity (i.e., well-defined porosity) allows to confine PSs isolate from each other, which is a quite important for avoiding self-quenching that would diminish their therapeutic efficiencies; (iii) rather than encapsulating the PSs molecules into the pores, photosensitizing organic ligands (e.g., porphyrins 182 and BODIPY 183,184 ) can be also incorporated as linkers within the MOF structure; (iv) their high porosity facilitates the diffusion of reactive oxygen species (ROSs), allowing 3 O 2 and 1 O 2 to diffuse freely in and out of the framework; (v) their intrinsic biodegradability 185 and minimal toxicity 171,179 by judicious choice of their composition (i.e. metal ion and linker), as well as the possibility to be synthesized at the nanoscale (i.e., nanoscale MOFs, nMOFs) 171,178,186 provides MOFs with key requirements for bioapplications; (vi) nMOFs can be designed to be degraded/decomposed upon endogenous chemical triggers (e.g., pH, GSH 187,188 ) or even to be activated by external energy stimuli (i.e. light 189 Particularly, the TPETCF@MIL-100 system was tested both in vitro and in vivo on Although the discussed examples so far led to improved PDT effects, the therapeutic efficiency of PDT in a real scenario is severely limited by low concentration of O 2 in solid tumours (i.e.…”
Section: C Metal-organic Frameworkmentioning
confidence: 99%